Space Weather Into the 2030s: The 2024 Solar and Space Physics Decadal Survey - Noé Lugaz (Space Weather)
Abstract The report of the 2024 decadal survey for the solar and space physics community was released on 2024 December 5 and has space weather science and applications as a central goal to explore and safeguard humanity's home in space. I discuss some of the main recommendations associated with space weather that will drive our field in the next decade.